If that's -9 - 6x + 9, it simplifies to -6x
12x^2+10
6x + 9 + 2x = 8x + 9
6x^2
(3x - 30)(x + 8) can also simplify to 3(x - 10)(x + 8)
6x-2y
12
7x + 7 + 6x - 9 = 13x - 2
When you have an expression like 6x - 6x, you can simplify it by combining like terms. In this case, the two terms are identical, so when you subtract one from the other, you are left with 0. Therefore, the result of 6x - 6x is 0.
Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5
If you mean 'simplify': (3x + 5)/15 I simply divided the coefficients (numbers) by 2.
6x - 5 -5 = 0 6x -10 = 0 +10=+10 6x=10 x= about 1.4